Impact of blockchain technology on supply chain collaboration: A case study of JD Chain - Chen Zhirui (SHS Web of Conferences)
This study uses JD.com as a case study to explore blockchain technology’s application in supply chain management. By leveraging distributed ledgers, consensus mechanisms, smart contracts, and cryptographic techniques, blockchain effectively tackles problems related to privacy protection, information traceability, and authenticity within traditional supply chains. This paper examines JD’s blockchain framework and its impact on various supply chain functions, revealing that blockchain technology has markedly improved procurement efficiency, reduced costs, enhanced customer trust and sales revenue, optimized logistics operations, and streamlined management processes. Through its JD Chain platform, JD.com has boosted operational performance and economic value and offered valuable insights for smaller enterprises. Given the technical and financial constraints faced by smaller firms, it is recommended that they engage in open source blockchain communities hosted by larger organizations to lower information acquisition costs and share resources. This paper provides practical advice for enterprises considering the integration of blockchain technology into their supply chain management.